Characterization of inflammatory markers and transcriptome profiles of differentially activated embryonic stem cell‐derived microglia. Issue 6 (9th March 2016) - Beins, Eva; Ulas, Thomas; Ternes, Svenja; Neumann, Harald; Schultze, Joachim L.; Zimmer, Andreas
Abstract : Microglia, the immune cells of the CNS, are highly adaptive cells that can acquire different pro‐ and anti‐inflammatory activation states with distinct functions in CNS homeostasis and pathologies. To study microglial function in vitro, primary microglia or immortalized cell lines are commonly used. An alternative to these cells are embryonic stem cell‐derived microglia (ESdM). ESdM have previously been shown to be very similar to primary microglia in terms of expression profiles and surface molecules. In this study, ESdM and primary microglia were treated with different inflammatory stimulants to analyze their ability to adopt different activation states. Using quantitative real‐time PCR, comparative transcriptomics, ELISA, and flow cytometry, we found that different activation states can be induced in ESdM, which are similar to those found in primary microglia. These states are characterized by specific sets of inflammatory marker molecules and differential transcriptome signatures. Our results show that ESdM are a valuable alternative cell model to study microglial functions and neuroinflammatory mechanisms. GLIA 2016;64:1007–1020 Main Points: ESdM can be activated into different pro‐ and anti‐inflammatory activation states, which are comparable to those of primary microglia on whole transcriptome and protein level. ESdM can be considered a valuable substitute for primary microglia.